Study of TCP performance in multi-hop wireless ad hoc networks / Irman Shah Idris - Idris, Irman Shah (2006)
This paper studies TCP performance in multi-hop wireless network using IEEE 802.11 for channel access control. The multi-hop wireless network was setup on "chain" network topology that contains on 3 hops as intermediate nodes. The purpose is to examine and understand the concept of TCP performance environment that is being used in multi-hop wireless Ad Hoc networks and its implementation in the Wireless Local Area Network (WLAN). The network simulates on J-Sim to perform the TCP performances on throughput, sequence number and smoothed round trip time. The explanation of each TCP performance is due to observations and analysis of the packet loss in multi-hop wireless network.